Cystic ovarian teratoma as a novel tumor and growth hormone deficiency as a new condition presenting in Multiple Endocrine Neoplasia type 2B: Case reports and review of the literature - Pomahacova, Renata; Paterova, Petra; Nykodymova, Eva; Vaclavikova, Eliska; Sykorova, Pavla; Personova, Katerina; Katra, Ramir; Subrt, Ivan; Sykora, Josef (Biomedical papers, 2022)
Background. We describe early and typical nonendocrine symptoms of Multiple Endocrine Neoplasia type 2B (MEN2B) presented in our patients with de novo M918T mutation in the RET proto-oncogene in early childhood, however, the diagnosis of MEN2B and medullary thyroid carcinoma (MTC) was confirmed late, in the second decade of life. In this paper, we emphasize the possibility of growth retardation, growth hormone (GH) deficiency and ovarian teratoma as a new symptom of MEN2B. Case Reports. Advanced MTC with palpable mass on the neck and nonendocrine symptoms such as marfanoid habitus, thickened lips, mucosal neuromas led to the diagnosis in case 1 at the age of 13 years and GH deficiency and nonendocrine symptoms in case 2 at the age of 11 years. The earliest feature of MEN2B was alacrima and constipation. Patient 1 was operated on for a slipped femoral capital epiphysis and for a cystic ovarian teratoma. Conclusions. Improved awareness of nonendocrine signs of MEN2B could lead to earlier diagnosis, when surgical cure of MTC is possible. Alacrima is the first sign of MEN2B. We confirmed the possibility of growth retardation and GH deficiency in MEN2B, which had been previously rarely described. We suggest that patients with MEN2B may develop cystic ovarian teratoma, to the best of our knowledge, which has never been described so far in the literature. The results of this study could be used to guide further diagnosing of MENB2 at the early stage for better clinical outcome. We emphasize that MEN2B carries a risk for development of cystic ovarian teratoma as a novel tumor in this disease.
Keywords: multiple endocrine neoplasia type 2B; medullary thyroid carcinoma; growth hormone deficiency; ovarian teratoma